Cross-border mobility in the Meuse-Rhine Euroregion: impact of COVID-19 border restrictions on everyday activities and visiting social network members - van Bilsen, Céline J. A.; Brinkhues, Stephanie; Hoebe, Christian J. P. A.; Stabourlos, Christina; Moonen, Chrissy P. B.; Demarest, Stefaan; Hanssen, Daniëlle A. T.; van Loo, Inge H. M.; Savelkoul, Paul H. M.; Philippsen, Dirk; van der Zanden, Brigitte A. M.; Dukers-Muijrers, Nicole H. T. M. (Frontiers in Public Health, 2024)
Introduction Cross-border mobility (CBM) to visit social network members or for everyday activities is an important part of daily life for citizens in border regions, including the Meuse-Rhine Euroregion (EMR: neighboring regions from the Netherlands, Belgium, and Germany). We assessed changes in CBM during the COVID-19 pandemic and how participants experienced border restrictions. Methods Impact of COVID-19 on the EMR’ is a longitudinal study using comparative cross-border data collection. In 2021, a random sample of the EMR-population was invited for participation in online surveys to assess current and pre-pandemic CBM. Changes in CBM, experience of border restrictions, and associated factors were analyzed using multinomial and multivariable logistic regression analysis. Results Pre-pandemic, 82% of all 3,543 participants reported any CBM: 31% for social contacts and 79% for everyday activities. Among these, 26% decreased social CBM and 35% decreased CBM for everyday activities by autumn 2021. Negative experience of border restrictions was reported by 45% of participants with pre-pandemic CBM, and was higher (p < 0.05) in Dutch participants (compared to Belgian; aOR= 1.4), cross-border [work] commuters (aOR= 2.2), participants with cross-border social networks of friends, family or acquaintances (aOR= 1.3), and those finding the measures ‘limit group size’ (aOR= 1.5) and ‘minimalize travel’ (aOR= 2.0) difficult to adhere to and finding ‘minimalize travel’ (aOR= 1.6) useless. Discussion CBM for social contacts and everyday activities was substantial in EMR-citizens, but decreased during the pandemic. Border restrictions were valued as negative by a considerable portion of EMR-citizens, especially when having family or friends across the border. When designing future pandemic control strategies, policy makers should account for the negative impact of CBM restrictions on their citizens.